Cul-de-sac [videorecording (DVD)] - Polanski, Roman; Pleasence, Donald; Dorléac, Françoise; Stander, Lionel (Criterion collection (DVD videodiscs), 2011)
When a gangster invades the isolated home of a quiet, kinky American and his willful French wife, the three begin a game of sexual and emotional humiliation.